Preimaginal stages of Acostatrichia simulans Mosely 1939, a Neotropical microcaddisfly (Trichoptera: Hydroptilidae: Leucotrichiinae) - Angrisano, Elisa B. (2010)
The preimaginal stages and cases of Acostatrichia simulans Mosely 1939, collected in Salto Encantado Provincial Park (Misiones province, Argentina) are described. This is the first description of the immature stages of this genus, and its first record from Argentina. The larvae were collected manually and transported to the laboratory, where they completed their development. Their identity was established using the metamorphotype method. They show strong resemblance to the larvae of Abtrichia Mosely, Anchitrichia Flint, Ceratotrichia Flint, Leucotrichia Mosely and Zumatrichia Mosely, especially to Zumatrichia.